Middle landscape in portraying the Malay national identity / Kamarul Bahrain Shuib …[et al.] - Shuib, Kamarul Bahrain; Hashim, Habsah; Sulaiman, Suria; Abdullah, Marina (2014)
Colonization often shaped the minds of the population they settled for generations. Studies have shown that people of colonized countries tended to follow the colonization perceptions of the country like valuing the natural landscapes, biodiversity, urban historical past or the wild forests. In Malaysia, one area that was left out and not valued is the middle landscape; the common ordinary land called the Malay heartland. The purpose of this research was to explore the value of middle landscape as perceived by the community. There is a lack of attention given in conserving our national landscape especially the middle landscapes. Literature in landscape research has shown that national identities are formed by the culture that had shaped the landscape over time. Middle landscapes are rural landscapes of villages, agriculture and pastoral lands inhabited by the Malays. Thus, conserving the cultural landscape is significant to ensure that it is not taken up by rapid development, climate change and also other threats. To achieve the goal of research, three objectives had been developed namely to identify important elements in a landscape, to find the value of landscape and to recommend fundamental ways to improve public understanding in landscape conservation. Methods used to gather data are visual observation, survey questionnaires and interviews. Observation includes inventory of landscape properties as guided by a set of criteria and photographs of landscape as surrogates of the middle landscape. Selected photographs will be used in the questionnaires which will consist of demographic profile and Likert-scale questions. Interviews will also be conducted to support data needed. The expected outcome shall be landscape values as highlighted by the communities and these in turn help to strengthen the landscape conservation strategies.